30-Day Readmissions and Coordination of Care Following Endoscopic Transsphenoidal Pituitary Surgery: Experience with 409 Patients - Ghiam, Michael K.; Chyou, Darius E.; Dable, Cortney L.; Katz, Andrew P.; Eichberg, Daniel G.; Zhang, Hang; Ayala, Alejandro R.; Kargi, Atil Y.; Komotar, Ricardo J.; Sargi, Zoukaa (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective The study aimed to (1) quantify readmission rates and common causes of readmission following endoscopic transsphenoidal pituitary surgery (ETPS); (2) identify risk factors that may predict readmission within 30 days; (3) assess postoperative care coordination with endocrinology follow-up; and (4) identify patients for whom targeted interventions may reduce 30-day readmissions.Methods Retrospective quality improvement review of patients with pituitary adenoma who underwent ETPS from December 2010 to 2018 at a single tertiary care center.Results A total of 409 patients were included in the study, of which 57 (13.9%) were readmitted within 30 days. Hyponatremia was the most common cause of readmission (4.2%) followed by pain/headache (3.9%), cerebrospinal fluid leak (3.4%), epistaxis (2.7%), hypernatremia (1.2%), and adrenal insufficiency (1.2%). Patients with hyponatremia were readmitted significantly earlier than other causes (4.3 ± 2.2 vs. 10.6 ± 10.9 days from discharge, p = 0.032). Readmitted patients had significantly less frequent outpatient follow-up with an endocrinologist than the nonreadmitted cohort (56.1 vs. 70.5%, p = 0.031). Patients who had outpatient follow-up with an endocrinologist were at lower risk of readmission compared with those without (odds ratio: 0.46; 95% confidence interval: 0.24–0.88).Conclusion Delayed hyponatremia is one of the most common causes of 30-day readmission following ETPS. Postoperative follow-up with an endocrinologist may reduce risk of 30-day readmission following ETPS.Implications for Clinical Practice A multidisciplinary team incorporating otolaryngologist, neurosurgeons, and endocrinologist may identify patients at risk of 30-day readmissions. Protocols checking serum sodium within 1 week of surgery in conjunction with endocrinologist to tailor fluid restriction may reduce readmissions from delayed hyponatremia.
Keywords: readmissions; transsphenoidal surgery; pituitary surgery; risk factors; endocrinology; coordination of care